Analysis of MLH1 and MSH2 Expression in Ovarian Cancer before and after Platinum Drug-based Chemotherapy - SAMIMI, G; FINK, D; VARKI, N. M; HUSAIN, A; HOSKINS, W. J; ALBERTS, D. S; HOWELL, S. B (Clinical cancer research, 2000)
Preclinical studies have demonstrated a relationship between DNA mismatch repair (MMR) status and sensitivity to cisplatin and carboplatin. MMR-deficient cells are resistant to both drugs, and selection for cisplatin resistance in vitro is sometimes accompanied by loss of MMR protein expression. We used immunohistochemical staining techniques to investigate hMLH1 and hMSH2 expression in paired ovarian tumor sections from 54 ovarian cancer patients before and after platinum-based therapy. We sought associations between hMLH1 and hMSH2 protein expression and clinical parameters known to be of prognostic significance as well as response to treatment and overall survival. hMLH1 and hMSH2 staining decreased significantly after platinum-based therapy. The percent of malignant cells that stained positive correlated with the intensity of nuclear staining for both proteins; staining for hMLH1 correlated well with staining for hMSH2. Unexpectedly, expression of nuclear hMLH1 correlated negatively with response to treatment. Expression of nuclear hMLH1 and hMSH2 was positively correlated with pretreatment CA125 level, and expression of nuclear hMSH2 was positively correlated with change in CA125 level after treatment. Tumor stage was associated with expression of nuclear hMSH2, and tumor histological subtype was associated with both hMLH1 and hMSH2 staining. No association was found between expression of either protein and overall survival. These results indicate that the tumor is biologically altered after chemotherapy consistent with treatment-induced selection for cells expressing lower hMLH1 and hMSH2 levels. However, immunohistochemical staining for either hMLH1 or hMSH2 was not highly predictive of drug sensitivity as measured by response or survival.